Suitable-habitat dynamics for wintering geese in China’s largest freshwater lake - Xia Shaoxia; Yu Dingkun; Cui Peng; Duan Houlang; Teng Jiakun; Yu Xiubo (Global Ecology and Conservation, 2021)
To maintain species population stability and ensure the ecological safety of internationally important wetlands, it is essential to be able to simulate suitable habitat for dominant species. Here, we describe a suitable-habitat model for wintering geese in the Poyang lake region of China, based on the Maximum Entropy modeling. The spatiotemporal patterns of suitable habitats produced by the model are analyzed by using species occurrence data from satellite tracking and environmental variables derived from remote sensing data. The results show that the normalized difference vegetation index predictor – representing productivity and food availability – made a considerable contribution to model prediction power, while the contribution from terrain data is relatively low. Nearly one third of the area of the entire floodplain can provide suitable habitats for geese during wintering periods (25.50% for Bean goose Anser fabalis and 29.57% for Greater white-fronted goose Anser albifrons). More than forty percent of the suitable habitats are located in the seasonally inundated sub-lakes, indicating that such sub-lakes play an indispensable role in maintaining goose habitats. In the sub-lakes, the area of suitable habitats for geese, per unit area, is 1.67–1.80 times than in the non-sub-lake areas of the floodplain. Therefore, the regulation of the sub-lakes during the dry season has important implications for the management of goose habitats.